Sudden cardiac death risk stratification in dilated cardiomyopathy: a state of the art review - B. Sh. Berdibekov; N. I. Bulaeva; S. A. Alexandrova; E. Z. Golukhova (Российский кардиологический журнал, 2025)
Dilated cardiomyopathy is one of the most common types of cardiomyopathy, characterized by left ventricular dilation and systolic dysfunction. The disease is accompanied by a high risk of adverse outcomes, including heart failure decompensation and sudden cardiac death (SCD). Traditionally, only left ventricular ejection fraction ≤35% was used to identify candidates for cardioverter-defibrillator implantation for the primary prevention of SCD. However, with the advances in therapy for heart failure, cardiac resynchronization therapy and modern cardiac imaging techniques such as delayed contrast-enhanced magnetic resonance imaging and genetic tests, SCD risk stratification approaches should be revised. This paper reviews the state of the art on SCD risk stratification in patients with dilated cardiomyopathy. Particular attention is paid to the role of magnetic resonance imaging and genetic studies, which significantly expand the potential of risk assessment and allow more accurate identification of patients requiring cardioverter-defibrillator implantation for primary SCD prevention.